Commuting in Belgian metropolitan areas: The power of the Alonso-Muth model - Verhetsel, Ann; Thomas, Isabelle; Beelen, Marjan (Journal of Transport and Land Use, 2010)
In order to understand patterns of urban commuter flows, insight is required into urban spatial structure (and vice versa). The present contribution first provides a concise overview of the theoretical perspectives from which economists and geographers approach commuting issues. Subsequently, the focus shifts to the classical spatial-economic urban models and how they explain commuter movements. We conduct a number of cluster analyses from which we are able to derive a commuting typology of city region areas. We conclude that distance (which also comprises journey time and proximity of traffic infrastructure), housing characteristics, housing environment, and income continue to play key roles in commuting patterns in the metropolitan areas under consideration.